Alone Together: Is Strain Experienced Concurrently by Members of Operating Room Teams?: An Event-based Study - Sandra Keller, PhD; Steven Yule, PhD; Douglas S. Smink, MD, MPH; Vivian Zagarese, BSc; Shawn Safford, MD; Fidel A. Valea, MD; Guido Beldi, MD; Sarah Henrickson Parker, PhD (Annals of Surgery Open, 2023)
Objective:. To identify which strain episodes are concurrently reported by several team members; to identify triggers of strain experienced by operating room (OR) team members during the intraoperative phase. Summary:. OR teams are confronted with many sources of strain. However, most studies investigate strain on a general, rather than an event-based level, which does not allow to determine if strain episodes are experienced concurrently by different team members. Methods:. We conducted an event-based, observational study, at an academic medical center in North America and included 113 operations performed in 5 surgical departments (general, vascular, pediatric, gynecology, and trauma/acute care). Strain episodes were assessed with a guided-recall method. Immediately after operations, participants mentally recalled the operation, described the strain episodes experienced and their content. Results:. Based on 731 guided recalls, 461 strain episodes were reported; these refer to 312 unique strain episodes. Overall, 75% of strain episodes were experienced by a single team member only. Among different categories of unique strain episodes, those triggered by task complexity, issues with material, or others’ behaviors were typically experienced by 1 team member only. However, acute patient issues (n = 167) and observations of others’ strain (n = 12) (respectively, 58.5%; P < 0.001 and 83.3%; P < 0.001) were often experienced by 2 or more team members. Conclusions and relevance:. OR team members are likely to experience strain alone, unless patient safety is at stake. This may jeopardize the building of a shared understanding among OR team members.